AUGMENTED REALITY IN CONTEMPORARY RELIGIOUS PRACTICE - Mylenka, Halyna; Anhelova, Anhelina (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2021)
The usage of the augmented reality is increasing in various religious fields. Virtual visualizations replace the theatrical elements with which church institutions used to operate in the past. The latest media technologies cause a specifically perception of religious ideas and symbols by believers. Consequently, augmented reality is a way of spectacularly visualizing religious topics, and new technologies have an effective impact on the consciousness of contemporary religious adherents. Thus the purpose to determine the main directions, functions, risks and perspectives of applying augmented reality in the religious education and practice of believers is very actual. Augmented reality is a convenient interactive method of forming parishioner’s knowledge, creeds and, ultimately, a steadfast belief in the importance of regular religious practice. The main target audiences for implementing such new technologies consists from children, youth, pilgrims and people with disabilities. Despite serious objections from opponents, the application of augmented reality in religious education and daily practice has a great potential. So the use AR-technology in different directions (learning game, interactive quizzes, animated guides, biblical and hagiographic stories visualization, praying prompts et cet.) is an interesting phenomenon of the religious practice. This methodology could be improved only in case of in close cooperation with teachers, priests and IT-professionals. Thus augmented reality needs their methodologically correct, gradual, controlled programmatic implementation in different religious fields. The phenomenon of dissemination of the latest technologies in the education and daily life of religious communities requires further scientific reflection.